DIVERSITY OF ZOOPLANKTON IN THREE MAJOR LAKES OF HUSNABAD SURROUNDING AREA, TELANGANA STATE, INDIA - KALPANA, B.; RANI, V. SWAROOPA; JYOTHILAXMI, A.; REDDY, T. RAVINDER (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
In the present study the three different lentic water bodies were selected for the quantitative estimation of zooplankton in the surrounding area of Husnabad division. The present work carried out for one year from 2019 to 2020. The selected lakes were distanced between 40 to 50 km from Kakatiya University campus. During the study period, 15 genera of zooplankton belonging to four major groups were observed. Among the total zooplankton 7 species belongs to Rotifera, 3 belongs to Copepoda, Cladocera each and 2 belongs to Ostracoda In all the four major groups the Rotifera group of zooplankton is dominated followed by Copepoda, Cladocera and Ostracoda. In the study period the highest number of zooplankton species observed in the summer season and lowest abundance observed in north east monsoon season in all the three lakes. The zooplankton results indicates that the selected three lakes were not much polluted and supports rich diversity.